Syndrome of populism and the evolution of post-Soviet regimes - Duvanova, Dinissa (Frontiers in Political Science, 2025)
The juxtaposition of “us” the people vs. “them” the elites and the demonization of outsiders have been the recurring themes across the post-Soviet space, from opposition party programs to the political rhetoric of chief executives. Is populism, often defined as a manifestation of nativism, anti-elitism, and xenophobia in party politics, social movements, policy, and leadership styles, a useful concept for the study of post-Soviet politics? To answer this question, I trace a range political manifestations of populism starting with the early years of transition, during the regime breakdowns, in participatory autocracies, and under the consolidating repressive dictatorships. A populist syndrome appears to be most pronounced in the context of democratic backsliding, contentious politics, and unconsolidated autocracies. As the post-Soviet autocratic regimes consolidate restrictive and non-participatory mechanisms of societal control (dominant parties, centralized propaganda machines, and repressive apparatus), populist tactics become less prevalent and populism as a concept describing elements of political life becomes more problematic.